Expert System for Diagnosing Brain Tumors Using the Certainty Factor (CF) Method - Veri Arinal; Nuary Inaldi Simarmata (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The development of computer technology helps many aspects of life. One aspect of life that takes advantage of technological developments is the health sector, in order to solve problems including brain tumors. Brain Tumor Disease is the growth of abnormal cells in or around the brain in an unnatural and uncontrolled manner. Patients with brain tumors continue to increase every year, because the initial symptoms are often underestimated. Therefore created a software that can help diagnose brain tumors using the certainty factor method.